Strength training improves double poling performance after prolonged submaximal exercise in cross-country skiers - Øfsteng, S.; Sandbakk, O.; van Beekvelt, M.; Hammarström, D.; ristoffersen, K.; Hansen, J.; Paulsen, G.; Rønnestad, B. R. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The purpose of this study was to investigate the effects of adding strength training with or without vibration to cross-country (XC) skiers` endurance training on double-poling (DP) performance, physiological, and kinematic adaptations. Twenty-one well-trained male XC-skiers combined endurance- and upper-body strength training three times per week, either with (n = 11) or without (n = 10) superimposed vibrations for 8 weeks, whereas eight skiers performed endurance training only (CON). Testing included 1RM in upper-body exercises, work economy, neural activation, oxygen saturation in muscle, and DP kinematics during a prolonged submaximal DP roller ski test which was directly followed by a time to exhaustion (TTE) test. TTE was also performed in rested state, and the difference between the two TTE tests (TTEdiff) determined the ability to maintain DP performance after prolonged exercise. Vibration induced no additional effect on strength or endurance gains. Therefore, the two strength training groups were pooled (STR, n = 21). 1RM in STR increased more than in CON (P < .05), and there were no differences in changes between STR and CON in any measurements during prolonged submaximal DP. STR improved TTE following prolonged DP (20 ± 16%, P < .001) and revealed a moderate effect size compared to CON (ES = 0.80; P = .07). Furthermore, STR improved TTEdiff more than CON (P = .049). In conclusion, STR superiorly improved 1RM strength, DP performance following prolonged submaximal DP and TTEdiff, indicating a specific effect of improved strength on the ability to maintain performance after long-lasting exercise.